RF Magnetron Sputtering of Silicon Carbide and Silicon Nitride Films for Solar Cells - V.S. Zakhvalinskii; E.A. Piljuk; I.Yu. Goncharov; V.G. Rodriges; A.P. Kuzmenko; S.V. Taran; P.A. Abakumov (Журнал нано- та електронної фізики)
RF-magnetron nonreactive sputtering method from solid-phase target in argon atmosphere was used for obtaining thin silicon carbide and silicon nitride films, that are used for constructing solar cells based on substrates of single crystal silicon of p-type.